A Model of Exchange Rate Regime Choice in the Transitional Economies of Central and Eastern Europe - Klyuev, Vladimir (IMF Working Papers; Working Paper ;, 2001)
The paper develops a model of exchange rate regime choice centered on the trade-off between internal price stability and external competitiveness and allowing for institutional costs of altering exchange rate arrangements. The main implication of the model is a nonlinear relationship between the rate of inflation and the choice of regime for the next period. The model also suggests that a major inflationary shock-like the one to which all Central and Eastern European economies were subject when they allowed prices to be determined by the market-should give rise to a tightening of the exchange rate regime, followed by a gradual introduction of more flexibility as inflation subsides. A series of regressions on a sample of 13 Central and Eastern European economies yield results consistent with the hypothesis.